Morphology and morphometrics of Diotarus verrucifer (Stål, 1877), a pygmy grasshopper endemic to Mindanao - Mohagan, Alma B.; Coritico, Fulgent P.; Melencion, Merced G.; Leaño, Emmanuel P.; Patano, Jr., Romeo R.; Amoroso, Victor B. (2020)
Diotarus Stål, 1887 (Tetrigidae: Cladonotinae) is a genus of pygmy grasshoppers with four species, all of which are inhabiting the Philippines with one species known also from Sulawesi. Diotarus verrucifer Stål, 1877 was originally described from Semper?s collection and from an unknown location from the Philippines. The species has been reported once since the description by GÅ¯nther in 1938. In this study, we report species diagnostic characteristics and describe its natural habitat. The brief morphological description and, more importantly, the updated distribution map are firsts for this species. The species is similar to Diotarus galeatus and is still not clear if they represent separate species. We present detailed measurements of our specimens in order to make comparison in the future possible. (Author's abstract)
Includes bibliographical references (page 569)
Keywords: Biology; Diotarus verrucifer; Groundhopper; Marilog district; Measurements; Mt. agad-agad.; Pronotum; Tectiform